Effects of Maren Pills on the Intestinal Microflora and Short-Chain Fatty Acid Profile in Drug-Induced Slow Transit Constipation Model Rats - Zhan, Yu; Wen, Yong; Du, Li-juan; Wang, Xiao-xiang; Tang, Shi-yu; Kong, Peng-fei; Huang, Wei-guo; Tang, Xue-gui (Frontiers in Pharmacology, 2022)
Background: Slow transit constipation (STC) is becoming a common and frequently occurring disease in today’s society, and it is necessary to explore the safe and effective treatment of STC. Method: Our study aimed to investigate whether the laxative effect of Maren pills (MRW) is associated with the regulation of intestinal microflora and intestinal metabolism in the colon. Loperamide hydrochloride-induced STC rats received MRW intragastrically for two consecutive weeks to evaluate the laxative effect of MRW involving the regulation of intestinal microflora, intestinal metabolism, and 5-HT signaling pathway. Intestinal microflora was detected by 16s rDNA sequencing, intestinal metabolism of short-chain fatty acids (SCFAs) was detected by HPLC, and the 5-HT signaling pathway was detected by WB, ELISA, immunofluorescence, and immunohistochemical analysis. Results: Our results revealed that the treatments with MRW increased not only the body weight, 24-h fecal number, 24-h wet fecal weight, 24-h dry fecal weight, fecal water content, and the intestinal propulsion rate but also the colonic goblet cell number, colonic Muc-2 protein expression, and colonic mucus layer thickness in the STC model rats. Moreover, MRW activated the 5-HT pathway by increasing the levels of 5-HT, 5-HIAA, 5-HT4R, CFTR, cAMP, and PKA in the colon tissue of STC rats. The 16S rDNA sequencing results showed that MRW improved the colonic microflora structure in colonic contents of STC rats, mainly by increasing Lactobacillus and decreasing Prevotella. Finally, we found that MRW regulated the SCFA metabolism in the colonic contents of the STC rats, mainly by increasing the contents of acetic acid, propionic acid, and butyric acid; the relative abundance of Lactobacillus was positively correlated with either contents of acetic acid, propionic acid, and butyric acid, and the relative abundance of Clostridium was negatively correlated. Conclusion: Our study further showed that MRW could improve constipation in STC rats, and the mechanism may be by regulating the intestinal microflora structure and improving the metabolism of SCFAs.